Diversity of Banana Plant Types (Musa spp) in Kuala Dua Village, Sungai Raya District, Kubu Raya Regency - Rodiyeh, Rodiyeh; Linda, Riza; Ifadatin, Siti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This research aims to determine the diversity and relationships of banana varieties (Musa spp) based on morphological characters. This research was conducted from January to April 2023 in 4 hamlets, namely Dusun Keramat 1, Dusun Keramat ll, Dusun Karya l, and Dusun Kary ll in Kuala Dua Village, Sungai Raya District, Kubu Raya Regency, West Kalimantan. There were 41 morphological characters observed including vegetative, generative and quantitative characters. Analysis of kinship relationships using the UPGMA (Unweighted Pair-wise Multivariate Analysis) method with the NTSYS ver 2.0 application is presented in the form of a dendrogram. In this research, 13 varieties were obtained, namely kapok bananas, crew bananas, 40 day bananas, cavendish bananas, green cooking bananas, chestnut bananas, mas bananas, Malaysian bananas, king bananas, areca nut bananas, Ambon bananas, red kak bananas, and prawn bananas. The results of the grouping analysis showed that 13 banana varieties had a similarity level of 39% and formed two main groups, namely groups A and B. Group A consisted of kapok bananas, crew bananas, red kak bananas, chestnut bananas, king bananas, areca nut bananas and prawn bananas. Group B consists of 40 day bananas, mas bananas, cavendish bananas, green ripe bananas and Malaysian bananas. At a similarity level of 83%, each banana variety forms a group within its respective variety.